Application of Contextual Problems to Help Students Mathematic Understanding Ability in Science and Social Class Grades XI - Anin, Fendy Reza; Dirgantoro, Kurnia Putri Sepdikasari (Universitas Wiralodra, 2023)
Learning mathematics aims to instill the ability to understand mathematics. This ability is important because it trains students to think deductively and realize the relationship between mathematical concepts in real life. Field facts prove that XI IPA IPS students from a private high school in the Lampung area have difficulty working on contextual questions as a result of their low ability to understand mathematics. The purpose of this research is to analyze the implementation of contextual questions in helping students' mathematical understanding abilities. The subjects in this study were 21 students of class XI IPA IPS at a private school in Lampung. The research method used is descriptive qualitative and data collection through written tests and interviews. The results of the study show that contextual questions can help students' mathematical understanding abilities. Through the results of this study, it is suggested that schools provide training in making contextual questions, teachers need to use contextual questions in learning, and further researchers expand the variables reviewed.